Diversidad social en las pautas periodísticas: el caso de las periferias paulistanas - Nonato, Cláudia (Universidade de São Paulo | Escola de Comunicações e Artes, 2020)
This article presents the results of the quantitative stage of the research The production of news from the outskirts of São Paulo: profile, routines and new configurations of journalistic work, whose objective was to investigate the profile of journalists who produce information from and about the periphery of São Paulo in new alternative economic arrangements (Figaro; Nonato, 2017). To fulfill this objective, make a brief reflection on the lack of plurality of the Brazilian media, analyze how approximations and differences between local, public, against hegemonic and peripheral journalism and present a methodology adopted for a research. As recent results, verifiable for journalists are young people, just over five years in the profession and do not have a clear opinion about respect for the concept of peripheral journalism.